Case Report: Lung adenocarcinoma associated with germline ERCC2 frameshift mutation - Liu, Lili; Cui, Jia; Liu, Siye; Pan, Evenki; Sun, Limin (Frontiers in Oncology, 2023)
Family history is an established risk factor for lung cancer. Previous studies have found that germline genetic alterations, such as those in EGFR, BRCA1, BRCA2, CHEK2, CDKN2A, HER2, MET, NBN, PARK2, RET, TERT, TP53, and YAP1, are associated with an increased risk of developing lung cancer. The study reports the first of a lung adenocarcinoma proband with germline ERCC2 frameshift mutation c.1849dup (p. A617Gfs*32). Her family cancer history review demonstrated that her two healthy sisters, a brother with lung cancer, and three healthy cousins were positive for ERCC2 frameshift mutation, which might contribute to increased cancer risk. Our study highlights the necessity of performing comprehensive genomic profiling in discovering rare genetic alterations, early cancer screening, and monitoring for patients with family cancer history.